Analisis Permasalahan Calistung Pada Siswa Kelas III SD Muhammadiyah Birrul Walidain - Ahmad Ridlwan Imamuddin; Bagas Kurniawan (Badan Penerbit STIEPARI Press, 2024)
This study aims to analyze calistung problems in grade 3 students of SD Muhammadiyah Birrul Walidain. This research is a type of descriptive qualitative research that seeks an in-depth understanding of social phenomena in a natural way. The data collection technique used is by using interview, documentation and direct observation methods. Based on the data obtained from the results of the study, it shows that of the 26 students in the class, there is one student who still has difficulty in reading, writing and counting due to lack of learning experience at home, less innovative learning from teachers and lack of attention from parents and teachers to improve children's calistung skills. Therefore, teachers are required to be able to find innovations in learning strategies and implement differentiated learning to understand and differentiate students' learning styles from one another.